L’homosexualité comme objet de recherche anthropologique [1966] - David Sonenschein (Genre, Sexualité et Société)
After presenting literature produced by different disciplines on the topic of homosexuality, the author argues for his study of anthropology, not only in the geographic areas traditionally studied by the discipline, but also in modern Western societies, particularly to determine how certain key concepts of this discipline can be operationally deployed in the analysis of contemporary forms of homosexuality.